IT investment and Islamic banking performance in Indonesia: do sukuk issuance and shariah governance matter? - Effendi, Jaenal; Qoyum, Abdul; Wardhana, Leo Indra; Mohd Thas Thaker, Hassanudin (Business Perspectives, 2023)
IT investment and financial performance are crucial issues for the Islamic banking industry. An Islamic banking (IB) that is established in a technologically advanced setting, employs mostly young and tech-savvy employees, and adheres to Islamic principles in all aspects of its activities, needs to invest in IT. This investment in information technology is essential if they are to remain competitive and achieve solid financial performance. This study aims to investigate the effect of IT investment on Islamic banking performance in Indonesia. The study used data of 14 Islamic banks in Indonesia, from 2012 to 2021. By employing panel regression analysis, the study revealed that IT investment has a significant impact on Islamic banking performance, indicated by ATM and Expenses for Human Resources (BG), which has the coefficient 1.75e-07 (Alpha 0.060) and 4.73e-14 (Alpha 1%), respectively. The study also documented a significant relationship between IT investment and IB performance, caused by Sukuk issuance and the Shariah supervisory board. Sukuk issuance has a negative impact on banking performance in relation to IT investment, while shariah governance (board of directors and shariah supervisory board) has a positive impact. Hence, it is also important for an Islamic banking to minimize the use of Sukuk, which until now was still categorized as debt, and to maximize the role of good governance to back up IT spending.